PENGEMBANGAN APLIKASI ACIL (ASTRONOT CILIK) UNTUK MENINGKATKAN PEMAHAMAN SISWA SD PADA PEMBELAJARAN IPA ROTASI DAN REVOLUSI BUMI - Arini Delima Putri, - (2023)
This research is motivated by the large number of students who still do not understand the concept of the earth's rotation and revolution as a whole and there is often confusion when explaining the definition and impact of the earth's rotation and revolution. This is due to the limitations of the learning media used by the teacher when the learning process takes place, causing a lack of students' understanding of this material. Based on this, this study aims to improve students' understanding of the concept of phase C in elementary schools in learning science about rotational motion and earth's revolution. The research method used in this study is the Design and Development (D&D) method which was developed using the ADDIE development model through five stages, namely analysis, design, development, implementation, and evaluation. The development of the Acil application was carried out by researchers based on the learning outcomes in the independent curriculum. The results of the expert validation assessment in the form of a questionnaire showed that the Acil application was in a very appropriate and appropriate category for use in class VI elementary school learning. The Acil application was tested on Phase C Elementary School students through a pretest and posttest. The researcher also conducted an N-gain test from the results of the pretest and posttest that had been done by phase C students with the average calculation results showing that the Acil application was in the high increasing category. Based on this, it can be said that the development of learning media in the form of the Acil application is feasible to use and can increase elementary students' understanding of science concepts, especially in the material of rotational motion and earth revolution phase C in elementary schools.